Alpha-7 Nicotinic Receptor Dampens Murine Osteoblastic Response to Inflammation and Age-Related Osteoarthritis - Courties, Alice; Petit, Juliette; Do, Ariane; Legris, Manon; Kouki, Inès; Pigenet, Audrey; Sacitharan, Pradeep K.; Ehkirch, Francois-Paul; Berenbaum, Francis; Sellam, Jérémie (Frontiers in Immunology, 2022)
Introduction Osteoarthritis (OA) is a whole-joint disease characterized by a low-grade inflammation that is involved in both cartilage degradation and subchondral bone remodeling. Since subchondral bone has a cholinergic innervation and that acetylcholine (Ach) might have an anti-inflammatory effect through the α7 nicotinic Ach receptor (α7nAchR), we aimed (i) to determine the expression of non-neuronal cholinergic system and nicotinic receptor subunits by murine and human osteoblasts, (ii) to address the role of α7nAchR in osteoblastic response to inflammation, and (iii) to study the role of α7nAchR in a spontaneous aging OA model. Methods Primary cultures of WT and α7nAchR knock-out mice (Chrna7-/-) murine osteoblasts and of subchondral bone human OA osteoblasts were performed. The expressions of the non-neuronal cholinergic system and of the nAchR subunits were assessed by PCR. In vitro, IL1β-stimulated WT, Chrna7-/-, and human osteoblasts were pretreated with nicotine. At 24 h, expressions of interleukin-6 (IL6) and metalloproteinase-3 and -13 (MMP), RANK-ligand (RANKL), and osteoprotegerin (OPG) were quantified by qPCR and ELISA. Spontaneous aging OA was evaluated and compared between male WT and Chrna7-/- mice of 9 and 12 months. Results Murine WT osteoblasts express the main components of the cholinergic system and α7 subunit composing α7nAchR. Nicotine partially prevented the IL1β-induced expression and production of IL6, MMP3, and RANKL in WT osteoblasts. The effect for IL6 and MMP was mediated by α7nAchR since nicotine had no effect on Chrna7-/- osteoblasts while the RANKL decrease persisted. Chrna7-/- mice displayed significantly higher cartilage lesions than their WT counterparts at 9 and 12 months, without difference in subchondral bone remodeling. Human OA osteoblasts also expressed the non-neuronal cholinergic system and α7 subunit as well as CHRFAM7A, the dominant negative duplicate of Chrna7. Nicotine pretreatment did not significantly reduce IL6 and MMP3 production in IL-1β-stimulated human osteoarthritic osteoblasts (n = 4), possibly due to CHRFAM7A. Conclusion Cholinergic system counteracts murine osteoblastic response to IL-1β through α7nAchR. Since α7nAchR deletion may limit cartilage degradation during murine age-related OA, enhancing cholinergic system could be a new therapeutic target in OA but may depend on CHRFAM7A expression.